DURASI PERAWATAN OPTIMUM UNTUK FASILITAS PRODUKSI MINYAK DAN GAS DI KILANG TUBAN EAST JAVA - Yahya, Indra Nur; Mahatwan, Dian; Setiawan, Ari; Darmadi, Djarot B. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Electric Submersible Pump (ESP) is one of the most critical oil & gas equipment in Tuban East Java (TEJ) field. This research applies Reliability Centered Maintenance (RCM) to oil & gas to optimize maintenance methods for ESP at the TEJ field. The RCM was applied based on the historical failure events at equipment which caused Loss Production Opportunity (LPO). Start with Pareto chart, the RCM followed by Failure Modes and Effect Analysis (FMEA) that produced the Risk Priority Number (RPN) for the 80% problems. The last step provided the optimum maintenance periods using Weibull’s statistic. The result shows that flat cable in ESP has the highest RPN. Flat cable requires an optimum maintenance period of 509 days and a total cost of US59,342. The total cost consists of Periodic Maintenance (PM) and Risk costs.